Search for new phenomena with the monojet and missing transverse momentum signature using the ATLAS detector in root s=7 TeV proton-proton collisions - Onofre, A. (2011)
A search for new phenomena in events featuring a high energy jet and large missing transverse momentum in proton–proton collisions at View the MathML sources=7TeV is presented using a dataset corresponding to an integrated luminosity of 33 pb−1 recorded with the ATLAS detector at the Large Hadron Collider. The number of observed events is consistent with the Standard Model prediction. This result is interpreted in terms of limits on a model of Large Extra Dimensions.